The Consolidated Medium-Term Income and Expenditure Framework. (Policy Papers; Policy Paper ;, 2014)
The medium-term income projections have been updated since the last estimate provided to the Executive Board in April 2013. Lending income is higher compared with the earlier estimates as a result of new arrangements approved since April 2013. Non-lending income is lower primarily due to revised projections for investment income. The updated expenditure path assumes the net administrative budget remains constant in real terms at the FY 2014 level, implying a nominal medium-term path that is somewhat higher than in the April 2013 projections. Precautionary balances are projected to reach the current target of SDR 20 billion in FY 2018. The projections also illustrate a broad balance between income and expenditures even if lending were to return to pre-crisis levels.